I have an issue with the following problem:

Two quadratic equations have real roots $\alpha$ and $\beta$ such that $$\alpha - \beta = 3$$ and $$\alpha \beta = 2(\alpha + \beta).$$ Find the two possible quadratic equations that satisfy these conditions.

Since $\alpha$ is larger than $\beta$, in the general solution to the quadratic equation, familiarly:

$$x = \frac{-b\pm \sqrt{b^2-4ac}}{2a}$$

$\alpha$ needs to be the larger solution so it must be of the form:

$$\alpha = \frac{-b - \sqrt{b^2-4ac}}{2a}$$

since it's the bigger root, and $\beta$ is therefore:

$$\beta = \frac{-b + \sqrt{b^2-4ac}}{2a}$$

However, I need to find the two quadratic equations that have these roots.

If I play around a bit with the properties of the roots, I can work out some things like:

$$\alpha - \beta = 3$$

$$\frac{1}{2a}\ ((-b - \sqrt{b^2-4ac}) - (-b + \sqrt{b^2-4ac}) = 3$$

$$ - 2\sqrt{b^2-4ac} = 6a$$

$$4b^2 - 16ac = 36a^2$$

$$b = \frac{\sqrt{16a(2a - c)}}{2}$$

And the next property:

$$\alpha \beta = 2(\alpha + \beta)$$

$$\frac{-b - \sqrt{b^2-4ac}}{2a} \bullet \frac{-b + \sqrt{b^2-4ac}}{2a} = 2(\frac{1}{2a}(-b - \sqrt{b^2-4ac}+ -b + \sqrt{b^2-4ac}))$$


$$4c=\sqrt{16a(2a - c)}$$

$$16c^2 = 32a^2 - 16ac$$

$$0= 2a^2-ac -c^2$$


$$a= c$$ $$2a = -c$$

I'm going to assume these will represent both quadratics, so I'll use $a = c$ first.

$$b = \frac{\sqrt{16a(2a - c)}}{2}$$

$$b = \frac{\sqrt{16c(2c - c)}}{2}$$

$$b = \frac{\sqrt{16c^2}}{2}$$ $$b= \pm\ 2c$$

I'll use $b = 2c$ for equation one.

$$\frac{1}{2a}\ ((-b - \sqrt{b^2-4ac}) - (-b + \sqrt{b^2-4ac}) = 3$$

$$\frac{1}{2c}\ ((-2c - \sqrt{{4c}^2-4c^2}) - (-2c + \sqrt{{4c}^2-4c^2}) = 3$$


Obviously, I blew it, since that implies $a = b = c$. I'm not sure if what I did wrong was some technical errors or the wrong approach in itself. I'd appreciate any guidance on this.

  • $\begingroup$ You have the statement that "Since $\alpha$ is larger than $\beta$, we must have $\alpha= \frac{-b- \sqrt{b^2- 4ac}}{2a}$ and $\beta= \frac{-b+ \sqrt{b^2- 4ac}}{2a}$" but that is backwards. Then from "$\alpha- \beta= 3$, We have $\frac{-b+ \sqrt{b^2- 4ac}}{2a}- \frac{-b- \sqrt{b^2- 4ac}}{2a}= \frac{\sqrt{b^2- 4ac}}{a}= 3$ so that $\sqrt{b^2- 4ac}= 3a$ so that $b^2- 4ac= 9a^2$. But, frankly, I wouldn't do it that way. Instead write $a(x- \alpha)(x- \beta)= ax^2- a(\alpha+ \beta)x+ \alpha\beta= ax^2+ bx+ c$ so we must have $-a(alpha+ \beta)= b$ and $\alpha\beta= c$. $\endgroup$
    – user247327
    Jul 12 '17 at 18:22

The quadratic equation has the form


but $\alpha=3+\beta$ and

$$\alpha\beta=2(\alpha+\beta)\to (3+\beta)\beta=2(3+2\beta)$$

$$\beta^2-\beta-6=0\to \beta=-2 \text{ or }\beta=3$$

which give us $\alpha=1$ or $\alpha =6$, so we get the equations

$$x^2-(1-2)x+(1)(-2)=0\to x^2+x-2=0$$

$$x^2-(6+3)x+(6)(3)=0\to x^2-9x+18=0$$

  • $\begingroup$ Why do you know to put $(\alpha + \beta)$ as the constant for $bx$ in the quadratic? And why do you know to put $\alpha \beta$ as the constant $c $ in the quadratic? $\endgroup$
    – sangstar
    Jul 12 '17 at 18:17
  • $\begingroup$ @sangstar: because if $\alpha$ and $\beta$ are roots then you can write $(x-\alpha)(x-\beta)=x^2-(\alpha+\beta)+\alpha\beta$ $\endgroup$
    – Arnaldo
    Jul 12 '17 at 18:18
  • 1
    $\begingroup$ That's absolutely true... why did I not think of that.. thanks! $\endgroup$
    – sangstar
    Jul 12 '17 at 18:23
  • $\begingroup$ How do we know there's no constant attached to $x^2$? How do we know it's $ax^2$? $\endgroup$
    – sangstar
    Jul 13 '17 at 7:10
  • $\begingroup$ @sangstar: once we have a equation, we can simplify the $a$. $\endgroup$
    – Arnaldo
    Jul 13 '17 at 11:15

Suppose the quadratic equation whose roots are $\alpha, \beta$ is $x^2+bx+c=0$, then $$\alpha+\beta=-b\qquad \text{and} \qquad \alpha\beta=c.$$

So we need $\alpha+\beta$ and $\alpha\beta$

\begin{align*} (\alpha+\beta)^2 & = (\alpha-\beta)^2+4\alpha\beta\\ & = 9+8(\alpha+\beta)\\ t^2-8t-9&=0 && (\text{assume } t=\alpha+\beta)\\ t&=9,-1 \end{align*} So $$\alpha+\beta=9,-1 \qquad \text{ and } \qquad \alpha\beta=18,-2$$ So the two possible quadratics are: $$x^2-9x+18=0 \qquad \text{ and } \qquad x^2+x-2=0.$$

  • $\begingroup$ Where do you get that $\alpha + \beta = -b$ and $\alpha \beta = c$? $\endgroup$
    – sangstar
    Jul 12 '17 at 18:17
  • 1
    $\begingroup$ @sangstar THese are called Viete's relations or a simple way to understand is as follows: Since $x^2+bx+c=(x-\alpha)(x-\beta)=x^2-(\alpha+\beta)x+\alpha\beta$. Now compare the coefficients of both sides. $\endgroup$
    – Anurag A
    Jul 14 '17 at 18:02

It's much simpler to solve using Vieta's relations. Denote $s=\alpha+\beta$, $p=\alpha\beta$. Remember from high school that, if we know the values of $s$ and $p$, $\alpha$ and $\beta$ are the roots of the quadratic equation: $$x^2-sx+p=0.$$

The second condition becomes $p=2s$. As to the first, it is equivalent to $$(\alpha-\beta)^2=9\iff (\alpha+\beta)^2-4\alpha\beta=s^2-4p=9.$$ Taking into account the second relation, we obtain the quadratic equation $$s^2-8s-9=(s-4)^2-25=0,\quad\text{whence}\quad s=4\pm5=-1,9,\enspace p=-2, 18,$$ and the two quadratic equations: $$x^2+x-2=0,\qquad x^2-9x+18.$$

  • $\begingroup$ What implies the quadratic equation is of the form $x^2-sx+p$ and not $ax^2 \pm sx \pm p$? What implies such specific signage and lack of constant for $x^2$? $\endgroup$
    – sangstar
    Jul 13 '17 at 7:28
  • $\begingroup$ @sangstar: It doesn't imply whatever. This comes from the solution to a standard problem from high school (and actually a theorem): find two numbers, given there sum and their product. If the equation were, say, $ax^2+sx+p=0$, the sum of the roots would be $-s/a$, not $s$, and their product $p/a$. Also, if you factor out $a$ in your equation, you obtain the equation $x^2+\dfrac sa x+\dfrac pa=0$, which is a monic polynomial with the same solutions. $\endgroup$
    – Bernard
    Jul 13 '17 at 9:58

Let $\alpha$ and $\beta$ be the roots of the quadratic equation,



$$\alpha+\beta = -b/a \ \text{ and } \ \alpha\beta = c/a$$

Note: You can get these by,

$$\alpha+\beta = \frac{-b+\sqrt{b^2-4ac}}{2a} + \frac{-b-\sqrt{b^2-4ac}}{2a} = \frac{-b}{a}$$

$$\alpha\beta = \frac{(-b)^2 - (b^2-4ac)}{4a^2} = \frac{c}{a}$$

Now, using given conditions,

$$(\alpha - \beta)^2 = \alpha^2 + \beta^2 - 2\alpha\beta = 9 \\ \implies (\alpha+\beta)^2-4\alpha\beta = 9 \implies \alpha\beta^2 - 16\alpha\beta = 36 \implies \alpha\beta = \frac{16 \pm \sqrt{16^2+4\cdot 36}}{2}$$

$$\implies \alpha\beta = 8\pm10 = 18 \text{ or } -2$$

Now, use $\alpha+\beta = \alpha\beta/2 = 9 \text{ or } -1$

So, two quadratic equations are,

$$x^2 -9x+18= 0 \ \ \text{ and } \ \ x^2 +x -2 = 0$$

  • $\begingroup$ @sangstar I have derived $\alpha+\beta = -b/a, \alpha\beta=c/a$ $\endgroup$
    – no-one
    Jul 12 '17 at 18:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.